The Profile of Factors Influencing Condom Usage Among Transgender Population: A Systematic Review - Bin Patawari, Anwar Mohamad; Samsriyaningsih Handayani; Soetjipto; Abdul Khairul Rizki Purba (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Human Immunodeficiency Virus is still a problem around the world and in Indonesia, one of the most exposed is the Transgender community and one way to prevent HIV transmission is through condoms. This systematic review aims to find out the factors that influence condom use in transgender women. Literature searches were conducted using PubMed with the keywords 'transgender', 'peer support', 'knowledge', 'condom use'. From 202 studies that were screened using Preferred Reporting Items for Systematic review and Meta-Analyses (PRISMA), 2 studies were obtained and analyzed.: Data that was obtained such as research method, participants, exposure, and outcome such as condom use and their factors were obtained. Based on analyses on condom use factors, the knowledge of condom use is not as effective in improving condom use, another factor is that increase in trust causes the participants partners to not use condom as often, last factor is Peer support towards the partners has an increase in condom usage. Further research with other factors not found is needed to give better comparison